Formation of the component composition of blended hydrocarbon fuels as the problem of the multi-objective optimization; Chemical Engineering Journal; Vol. 383 - Ivanchina E. D. Emilia Dmitrievna; Ivashkina E. N. Elena Nikolaevna; Chuzlov V. A. Vyacheslav Alekseevich; Belinskaya N. S. Natalia Sergeevna; Dementjev A. Yu. Aleksandr Yurjevich (2020, 2020)
Title screen